Enhancing work performance: the role of communication and leadership styles - Kavitha Balakrishnan,; Ajitha Angusamy,; Riya Gunvantrai Patil,; Muhammad Nur Fitri Razak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Effective communication styles are essential to encourage understanding of expectations, effective workforce management, and organisational growth to stimulate employee work performance. This study explores the complex relationships between leadership styles, work performance, and communication styles. Employee commitment is found to have implications for organisational commitment aspects like responsibility, loyalty, and trust. Effective interpersonal and leadership communication encompasses relationships beyond and within the workplace. This study uses a questionnaire-based survey to investigate how leadership styles mediate the relationship between the factors of communication styles and job performance in Malaysian organisations. The perceptions of communication style, the mediating effect of leadership styles, and the relationship between communication style and job performance are investigated using quantitative data analysis using descriptive, inferential, and correlation tests to perform mediation analysis. The findings indicate the need for communication-focused training and engagement programmes and the significance of assertive communication styles for improved work performance. The study also establishes the critical need for leaders to comprehend the needs, motivations, and efficiency drivers of each team member. The study offers directions for future research, including larger geographic coverage, more communication variables, mixed-method techniques, and the investigation of other indirect effects. The study's conclusions give leaders practical advice on how to improve organisational communication for improved work performance and encourage employee trust and commitment.